J25 Performance Of The 36-item And 12-item Whodas 2.0 In Prodromal Huntington Disease. (17th September 2014) - Kim, J; Long, JD; Mills, JA; Downing, N; Williams, JK; Paulsen, J
Abstract : Background: The fifth edition of the Diagnostic and Statistical Manual for Mental Disorders (DSM-5) recommends the World Health Organisation Disability Assessment Schedule (WHODAS) 2.0 for routine clinical use. We tested the utility of the 36-item and 12-item WHODAS 2.0 in prodromal Huntington disease. Aims: The aims of the current study are (1) to test disease progression group differences in baseline values and longitudinal change in a separate analysis of participant and companion ratings on the 36-item and 12-item WHODAS 2.0; (2) to compare longitudinal participant and companion ratings on the 36-item and 12-item WHODAS 2.0, and; (3) to compare the 36-item and 12-item WHODAS 2.0 with the Total Functional Capacity (TFC) score, in terms of detecting baseline and longitudinal differences. Methods: Using data from 726 participants and 630 companions over a 3-year follow-up, linear mixed regression models were fitted and compared by Akaike's information criterion. Participants were classified into four groups based on their gene status and baseline disease progression (control, low, medium, and high progression). Results: For both the 36-item and 12-item WHODAS, participants and companions in the high group reported significantly worse functioning at baseline compared to controls. For longitudinal changes, companions but not participants in the medium and high groups reported significantly worse functional decline over time compared to controls. Participant and companion longitudinal trajectories showed divergence in the high group, suggesting reduced validity of self-report. The 12-item WHODAS detected longitudinal change better than the 36-item version and the TFC in the medium group. Conclusions: Both the 36-item and 12-item WHODAS 2.0 can detect baseline and longitudinal differences in prodromal HD, and may be useful in HD clinical trials. Companions may provide more accurate data as the disease progresses.